Effects of different preparation and cooking processes on the bioactive molecules of Allium vegetables - Katırcıoğlu, Beyza; Navruz-Varlı, Semra (Frontiers in Nutrition, 2024)
Allium species are among the most widely cultivated vegetables for centuries for their positive effects on human health and their variety of uses in food preparation and cooking. Preparation and cooking processes create chemical changes that can affect the concentration and bioavailability of bioactive molecules. Understanding the changes in bioactive compounds and bioactive activities in Allium vegetables resulting from preparation and cooking processes is essential for better retention of these compounds and better utilization of their health benefits. This study aimed to investigate the effects of different preparation and cooking processes on the bioactive molecules of Allium vegetables. This review concludes that bioactive compounds in Allium vegetables are affected by each preparation and cooking process depending on variables including method, time, temperature. Owing to differences in the matrix and structure of the plant, preparation and cooking processes show different results on bioactive compounds and bioactive activities for different vegetables. Continued research is needed to help fill gaps in current knowledge, such as the optimal preparation and cooking processes for each Allium vegetable.